Manajemen Kenaikan Tarif PAM Untuk Peningkatan Akses Air Bersih Bagi Seluruh Masyarakat - Utama, Chandra (Business Administration Study Program - Universitas Katolik Parahyangan, 2010)
World population growth causes increasing of demand for clean water. On the otherhand, at this moment, the Public water Utilities (PAMs) in various cities, especiallyin developing countries, unable to meet the needs of the entire population, especiallypoor families. Usually the price of piped water is very low. On the other hand, thepoor that no access to piped water pay more than the rich that have access.Usually, PAMs cannot serve the poor because they do not have fund to developthe new network. Furthermore, increase of water rates is necessary to collect moneyfor investment and service improvement. The tariff management must ensure allobjectives of public utilities such as: all families have minimum needs; water conversion;as well as PAMs have required profits are important in public water utilities.Very low tariff that make PAMs do not receive minimum profit for investment inservices and increase coverage area also directly make other objectives fail.The tariff plan of PAM Bandung municipality (PDAM) period 2006-2010 isused to describe tariff management planning. Actual condition in 2010 is also providedto compare the planning and result. Because limitation of data, this studyassume the planning is implemented.Based on the data, this study concludes that the tariff management of PDAM issuccess increase profit but fail improve household connections. Ironically, the connectionsfor the household go down and connections for the business go up. The tariffof PDAM, although they manage the increasing of tariff, cannot be categorized as thetariff increase to raise coverage area but increase to adjust the inflation.Keywords: water, public water utilities (PAMs), tariff, poor household